CHDH, a key mitochondrial enzyme, plays a diagnostic role in metabolic disorders diseases and tumor progression - Li, Yifei; Shen, Xinzhuang; Yang, Xiaowen; Lian, Fuming; Li, Yanping; Li, Jinmeng; Huang, Yongming; Shen, Wenzhi; Liu, Huan (Frontiers in Genetics, 2023)
Human choline dehydrogenase (CHDH) is a transmembrane protein located in mitochondria. CHDH has been shown to be one of the important catalytic enzymes that catalyze the oxidation of choline to betaine and is involved in mitochondrial autophagy after mitochondrial damage. In recent years, an increasing number of studies have focused on CHDH and found a close association with the pathogenesis of various diseases, including tumor prognosis. Here we summarized the genomic localization, protein structure and basic functions of CHDH and discuss the progress of CHDH research in metabolic disorders and other diseases. Moreover, we described the regulatory role of CHDH on the progression of different types of malignant tumors. In addition, major pathogenic mechanisms of CHDH in multiple diseases may be associated with single nucleotide polymorphism (SNP). We look forward to providing new strategies and basis for clinical diagnosis and prognosis prediction of diseases by diagnosing SNP loci of CHDH genes. Our work evaluates the feasibility of CHDH as a molecular marker relevant to the diagnosis of some metabolic disorders diseases and tumors, which may provide new targets for the treatment of related diseases and tumors.